Design of an energy efficient campus-based on energy audit report - Peter. J, Arun; Vijayadhasan. G, Keerthi (International Journal of Engineering and Technology, 2018)
Due to rapid urbanization and industrialization there is fast depletion of fossil fuels. Renewable energy resources contribute a considerable part in the Grid these days yet there is a mismatch between generation and consumption. The consumption of electrical energy is more than the electrical energy generated. It has become mandatory for us to conserve electrical energy in order to save the fuel reserves for our future generation. In this paper it is explained how an energy efficient institution can be made with the help of periodic Energy AuditÂ Â